Endoscopic hand-suturing for defect closure after gastric endoscopic submucosal dissection: a pilot study in animals and in humans - Goto, Osamu; Sasaki, Motoki; Akimoto, Teppei; Ochiai, Yasutoshi; Kiguchi, Yoshiyuki; Mitsunaga, Yutaka; Fujimoto, Ai; Maehata, Tadateru; Nishizawa, Toshihiro; Takeuchi, Hiroya; Kitagawa, Yuko; Yahagi, Naohisa (Endoscopy, 2017)
Background and study aims Mucosal suturing enables reliable and optimal defect closure after endoscopic treatments. We developed and investigated the feasibility of endoscopic hand-suturing (EHS) after gastric endoscopic submucosal dissection (ESD) in porcine in vivo models and in human clinical cases.Patients and methods EHS involving continuous suturing of the mucosal layers using a through-the-scope needle-holder and absorbable barbed suture, was performed after gastric ESD in six live pigs and in eight consecutive patients. Success rates, adverse events, and suture maintenance were subsequently investigated.Results EHS was successfully completed in all six pigs and eight patients (100 %) without severe adverse events. However, at 1 week postoperatively the suture closures had not been maintained in all six porcine cases and in the first four clinical cases. In the later four clinical cases, wider and tight suturing of the mucosal edges ensured that the defects remained closed until postoperative week 4.Conclusion EHS is a feasible procedure that may facilitate secure and refined endoscopic surgeries. Mucosal closure in such cases can be maintained using firm suturing.Clinical trial number: UMIN000017125